SARS‐CoV‐2 neutralization and serology testing of COVID‐19 convalescent plasma from donors with nonsevere disease. Issue 1 (2nd October 2020) - Gniadek, Thomas J.; Thiede, Joshua M.; Matchett, William E.; Gress, Abigail R.; Pape, Kathryn A.; Fiege, Jessica K.; Jenkins, Marc K.; Menachery, Vineet D.; Langlois, Ryan A.; Bold, Tyler D.
Abstract: Background: The transfer of passive immunity with convalescent plasma is a promising strategy for treatment and prevention of COVID‐19, but donors with a history of nonsevere disease are serologically heterogenous. The relationship between SARS‐Cov‐2 antigen–binding activity and neutralization activity in this population of donors has not been defined. Study Design and Methods: Convalescent plasma units from 47 individuals with a history of nonsevere COVID‐19 were assessed for antigen‐binding activity of using three clinical diagnostic serology assays (Beckman, DiaSorin, and Roche) with different SARS‐CoV‐2 targets. These results were compared with functional neutralization activity using a fluorescent reporter strain of SARS‐CoV‐2 in a microwell assay. Results: Positive correlations of varying strength (Spearman r = 0.37‐0.52) between antigen binding and viral neutralization were identified. Donors age 48 to 75 years had the highest neutralization activity. Units in the highest tertile of binding activity for each assay were enriched (75%‐82%) for those with the highest levels of neutralization. Conclusion: The strength of the relationship between antigen‐binding activity and neutralization varies depending on the clinical assay used. Units in the highest tertile of binding activity for each assay are predominantly comprised of those with the greatest neutralization activity.